Efficacy of combination therapy with probiotics and mosapride in patients with IBS without diarrhea: a randomized, double‐blind, placebo‐controlled, multicenter, phase II trial. Issue 5 (25th March 2015) - Choi, C. H.; Kwon, J. G.; Kim, S. K.; Myung, S.‐J.; Park, K. S.; Sohn, C.‐I.; Rhee, P.‐L.; Lee, K. J.; Lee, O. Y.; Jung, H.‐K.; Jee, S. R.; Jeen, Y. T.; et al.
Abstract: Background: Probiotics can be beneficial in irritable bowel syndrome (IBS). Mosapride citrate, a selective 5‐HT4 receptor agonist, stimulates gastrointestinal motility. We investigated the efficacy of combination therapy with probiotics and mosapride for non‐diarrheal‐type IBS. Methods: Two hundred and eighty‐five IBS patients were randomly assigned to either a combination of probiotics ( Bacillus subtilis and Streptococcus faecium ) and mosapride at one of four different doses or a placebo for 4 weeks. The primary outcome was the proportion of patients experiencing adequate relief (AR) of global IBS symptoms at week 4. The secondary outcomes included subject's global assessment (SGA) of IBS symptom relief, individual symptoms, stool parameters, and IBS‐quality of life. Key Results: The proportion of AR at week 4 was significantly higher in all treatment groups compared to the placebo group (53.7% in group 1, 55.0% in group 2, 55.2% in group 3, 53.6% in group 4 [the highest dose], and 35.1% in placebo group, respectively, p  < 0.05). The proportion of patients reporting 'completely or considerably relieved' in the SGA was higher in the treatment groups than in the placebo group. The abdominal pain/discomfort score in the treatment group 4 was more prominently improved compared with that of the placebo group. In patients with constipation‐predominant IBS, the improvements in stool frequency and consistency were significantly higher in the treatment groups 4 and 1, respectively, than those in the placebo group. Conclusions & Inferences: Combination therapy with probiotics and mosapride is effective for relief of symptoms in patients with non‐diarrheal‐type IBS. The study has been registered in the US National Library of Medicine (http://www.clinicaltrials.gov, NCT01505777). Abstract : The combination therapy with probiotics and mosapride is effective and safe for managing IBS symptoms and stool frequency and consistency in patients with non‐diarrheal‐type IBS. The highest dose of the study drug was most effective for producing improvement in abdominal pain/discomfort and spontaneous complete bowel movements.